2019
DOI: 10.3390/s19102401
|View full text |Cite
|
Sign up to set email alerts
|

Using of Multi-Source and Multi-Temporal Remote Sensing Data Improves Crop-Type Mapping in the Subtropical Agriculture Region

Abstract: Crop-type identification is very important in agricultural regions. Most researchers in this area have focused on exploring the ability of synthetic-aperture radar (SAR) sensors to identify crops. This paper uses multi-source (Sentinel-1, Sentinel-2, and Landsat-8) and multi-temporal data to identify crop types. The change detection method was used to analyze spectral and indices information in time series. Significant differences in crop growth status during the growing season were found. Then, three obviousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 63 publications
(87 reference statements)
0
60
0
1
Order By: Relevance
“…The work by Ban et al suggested that apart from speckles, the single parameter, high incidence angle SAR system used in their study did not provide sufficient differences to differentiate some crop species [15]. Thus, due to the limited viewing angles and orbits of available SAR data in most study cases, the sole use of SAR data may not be sufficient for crop type classification, especially in complex cropping systems.By the synergic use of microwave Sentinel-1 features and optical Sentinel-2 features, the accuracy of crop discrimination can be potentially improved [15][16][17][18]. However, despite the existing studies to combine SAR and optical images for crop classification, few studies (1) explored the performance of individual InSAR products (such as coherence, amplitude dispersion, and master versus slave intensity ratio) in crop type identification.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The work by Ban et al suggested that apart from speckles, the single parameter, high incidence angle SAR system used in their study did not provide sufficient differences to differentiate some crop species [15]. Thus, due to the limited viewing angles and orbits of available SAR data in most study cases, the sole use of SAR data may not be sufficient for crop type classification, especially in complex cropping systems.By the synergic use of microwave Sentinel-1 features and optical Sentinel-2 features, the accuracy of crop discrimination can be potentially improved [15][16][17][18]. However, despite the existing studies to combine SAR and optical images for crop classification, few studies (1) explored the performance of individual InSAR products (such as coherence, amplitude dispersion, and master versus slave intensity ratio) in crop type identification.…”
mentioning
confidence: 99%
“…By the synergic use of microwave Sentinel-1 features and optical Sentinel-2 features, the accuracy of crop discrimination can be potentially improved [15][16][17][18]. However, despite the existing studies to combine SAR and optical images for crop classification, few studies (1) explored the performance of individual InSAR products (such as coherence, amplitude dispersion, and master versus slave intensity ratio) in crop type identification.…”
mentioning
confidence: 99%
“…These data, which are distributed free of charge, have an average revisit time of two days between 0 and 45 degrees latitude [18]. As a result, Sentinel-1 data have been widely used for land cover classification [19][20][21], monitoring of phenology [22], and biomass or production estimation. The interferometric wide-swath (IW) mode that offers VV (vertical transmit and receive) and VH (vertical transmit, horizontal receive) polarization data is normally used as the default acquisition mode [23,24].In addition to C-band SARs, the high sensitivity of the sigma naught of X-band sensors has been confirmed, and the potential of the X-band for identifying and forecasting crop growth using indices such as LAI has widely been confirmed [25,26].…”
mentioning
confidence: 99%
“…More detailed information of the SAR data used in this study is provided in Table 1. We preprocessed these SAR data with SARscape 5.2, including multi-look, coregistration, speckle filtering (a 5 × 5 window Lee filter [34]), geocoding, and radiometric calibration [14]. These images were geocoded using the ASTER GDEM and their digital numbers (DN) were converted to decibel (dB) scale backscatter coefficients.…”
Section: Remote Sensing Variablesmentioning
confidence: 99%